(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2011)
This study evaluated the association of N-hexyl-2-methyl-4-nitroimidazol, a model drug, to aggregates formed by anionic polyelectrolytes on aqueous solution. The alternating copolymers of maleic anhydride and N-vinyl-2-pyrrolidone were synthesized and then modified by reaction of the anhydride groups with aliphatic amines and alcohols of varying length of the alkyl chain. The partition of the model drug between water and the hydrophobic microdomains provided by the copolymers was studied using the pseudo-phase model to determinate the distribution coefficient K S, and the standard free energy of transfer ∆µ°t. The results indicate that all copolymers assessed are potential pharmaceutical reservoirs of the model drug. Nevertheless, the solubility of N-hexyl-2-methyl-4-nitroimidazol on the polymeric solutions is independent from the length of the alkyl chain of the copolymer.